Putting the puzzle together: linking physiological and psychological determinants of health = (NsKLADANNQ PAZLU(B: (NZW(B'(NQZOK F)QÆZÆOLOGÆ^NOÇ TA PSIHOLOGÆ^NOÇ DETERMÆNANT ZDOROW(B'(NQ (B/s)E - Sira, Natalia (2018)
The article deals with the problems of physiological and psychological determinants of health. It has been shown that being able to understand how the experiences children affect lifelong outcomes in mental and physical health of individuals connecting the core capabilities adults need to thrive as parents and professionally in order to reach fullest developmental potential
(Nu STATT)QÆ WISWÆTLENO PROBLEMI FÆZÆOLOGÆ^NIH TA PSIHOLOGÆ^NIH ^INNIKÆW ZDOROW(B'(NQ(B. (NzASWÆD^ENO(B, (N]O DOSWÆD(B, (NOTRIMANIJ W DITINSTWÆ(B, (NWPLIWAÃ NA REZULXTATI PODALX[OGO VITTQ OSOBISTOSTÆ(B.s)E
(Nb)QÆBLÆOGR(B. (NW KÆNCÆ ST(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NZDOROW(B'(NQs; (NF)QÆZÆOLOGÆQs)E; (NPSIHOLOG)QÆQs)E; health; physiology; psychology